Nitrificação parcial/anammox aplicada a efluente anaeróbio doméstico : investigação de parâmetros operacionais e configurações do sistema com vistas à otimização do processo - Brenda Gonçalves Piteira Carvalho (2024)
The partial nitrification/anammox (PN/A) process is promising for achieving sustainability in wastewater treatment plants (WWTPs). However, its application for different wastewaters and applied loads, the impacts of reactor configuration, different aeration strategies and temperature are not fully understood. Furthermore, the startup of new anammox reactors in the absence of inoculum with anammox activity has been a challenge for implementing new anammox systems. Therefore, this work had the following objectives:1) to evaluate different strategies (aeration and temperature) for developing the PN/A process for removing nitrogen from anaerobically pretreated sewage; 2) to evaluate the dynamics of nitrous oxide (N2O) and methane (CH4) under different aeration conditions and influent load for PN/A; 3) to verify the feasibility of starting anammox system by applying both anaerobically pretreated sewage and aeration to PN/A, using activated sludge as inoculum and 4) to investigate the effects of applying low and high load effluents on PN/A, N2O emission and CH4 and in the microbial community. For this, sequential batch and fixed-bed foam with continuous flow reactors were used. The main results regarding objective 1 show that the decrease in temperature from 35°C to room temperature (20 to 29°C) did not limit the anammox process (TN removals 71 and 75%, respectively) and that the best aeration strategy intermittent consisted of 7 min on/14 min off, resulting in a median NT efficiency of 59%, and effluent with a median TN concentration of 15 mg/L. Regarding objective 2, it was verified that the aeration time for NP/A (1 to 7 min) favored the reduction of N2O emission rates. The most diverse group of microorganisms were heterotrophic denitrifying bacteria. The results of objective 3 show TN removal efficiency of 63 and 45% in reactors fed (from start-up) with autotrophic culture medium and anaerobically pretreated sewage under aeration, respectively. Nitrogen removal in both reactors increased after 60-70 days of start of operation. It was verified in the results of objective 4 that the increase in load caused by feeding with domestic anaerobic effluent and anaerobic sludge (3:1) caused TN removal of 43% and emission of N2O and CH4 per applied load of NT and COD of 0.021 and 1.022%, respectively. Finally, this study helps to elucidate issues related to operational strategies in anammox reactors and contribute to the dissemination of this technology in Brazil and warm climate regions in general.